Restrição de tiamina no período perinatal, induz, em animais na idade adulta, déficits motores e alterações em parâmetros centrais GABAérgicos e glutamatérgicos - Talita Helen Ferreira e Vieira (2009)
Thiamine, also known as vitamin B1, is an essential nutrient required by all tissues including the nervous system. In a previous study our group has shown that the maternal thiamine deficiency can lead to decrease in brain weight and changes in central neurochemical parameters assessed in the offspring. Considering the importance of thiamine to brain development, including motor systems the purpose of the present study was to investigate the effects of partial thiamine deficiency, during the perinatal period, on the motricity and neurochemical parameters in adult rats. Twenty male Wistar rats (weight = 437±41g) were used (ten of them born from normally-fed control mothers: CM and the other ten frommothers fed with thiamine-restrict diet RM. All the animals were submitted to motor tests (rotarod and paw print). After behavioral tests the rats were killed and their brain areas (thalamus, cerebellum and spinal cord) separated for glutamate and GABA analysis by HPLC. Observed that animals from RM group showed significant reduction of time spent on the rotarod [Mann-Whitney U = 12,50; p = 0,01] and increase in hind-base width [MC = 4,30±0,18; MR = 4,94±0,20; F(1,16) = 5,40; p = 0,03]. The treatment also affected significantly the concentrations of glutamate in cerebellum [MC = 5219,31±1071,13; MR = 3999,24±421,39; F(1,16) = 11,01; p = 0,00] and GABA in thalamus [MC = 192,11±33,00; MR= 250,64±65,54; F(1,16) = 5,26; p = 0,04]. For animals from CM group there was significant correlation between the performance on the rotarod and thalamus GABA concentration [r = - 0,73; p = 0,04] and between the average hind-base width and both thalamus [r = -0,86; p = 0,006] and cerebellum [r = 0,73; p = 0,04] GABA concentration. For animals from the RM group there was significant correlation between the stride length and the cerebellum GABA concentration [r = -0,71; p = 0,02]. These results indicates that thalamus GABAergic circuits are important for aspects of motor function and that the maternal thiamine restriction duringthe early stages of development can induce motor deficits and neurochemical changes in offspring that persist in later periods of life.